Types of Neotropical Mycetophilidae (Diptera) at the Natural History Museum collection, London - Amorim, Dalton De Souza; Oliveira, Sarah Siqueira (Zootaxa, 2013)
The primary types, secondary types, and some other identified specimens of 407 Neotropical species of Mycetophilidae at the Natural History Museum, London were examined. Notes were made on the condition of the primary types, their labels, and presence of other specimens in the type series. Additional comments are made about types, secondary types and some few other cases worth of note mistakenly determined to be at the NHM. Lectotypes are designated for syntypes of 17 species: Epicypta insipiens (Williston), Epicypta dolosa (Williston), Leia amabilis Williston, Leia concinna (Williston), Leia nitens (Williston), Megalopelma cellularis Edwards, Megalopelma fraudulenta (Williston), Megalopelma platyura Edwards, Mycetophila borgmeieri Edwards, Mycomya meridionalis Johannsen, Monoclona digitata Edwards, Mycomya peruviana Edwards, Neoempheria maculipennis Williston, Procycloneura paranensis Edwards, Stenophragma nigricauda Edwards, Tetragoneura simplex Edwards, Trizygia nitens Edwards. Three species–Leia biamputata Edwards, Leia fuscicornis Edwards, and Neallodia flavida Edwards–previously considered subjective junior synonyms in the literature were revalidated. Mycetophila rufoides nom. nov. is proposed for Mycetophila rufa Lane (preocc. Macquart 1826). Mycetophila dolosa Williston is transferred to Epicypta, without being assigned to a particular subgenus. The type of Sceptonia paiaguensis Freeman is formally considered lost. Photographs taken of holotypes and lectotypes are included, helping taxonomic documentation and in some extent, species identification. After the nomenclatural acts in this paper, the Natural History Museum, London, now holds holotypes of 292 Neotropical species of the Mycetophilidae, 23 lectotypes, syntypes of 3 species that have syntypes in other collections, paratypes of 81 species that have holotypes in other collections, identified specimens of 5 species with types lost and specimens of three species which fit in other cases.